A new design for an ultra-wideband microwave metamaterial absorber. (14th May 2021) - Yu, Yongjun; Sun, Pingyuan; Wang, Yunfan; Chen, Zhaoyang
Abstract: In this paper we propose a new design for an ultra-wideband microwave metamaterial absorber. This metamaterial absorber has a sandwich structure, and the top metal pattern is periodically arranged on the copper background. This metamaterial absorber is combined with Fe–Co composites and metamaterials, which solves the narrow-band problem of microwave absorption. We realize an absorptivity of more than 90% in the 2.16–18 GHz frequency band for normal incidence. The thickness of the structure is 0.61 mm (about 1/48.8 wavelength at the central frequency). The performance of the proposed absorber is not sensitive to the polarization of incident waves.